Mechanisms of free radical oxidation of unsaturated lipids - Porter, Ned A.; Caldwell, Sarah E.; Mills, Karen A. (Lipids, 1995)
The primary producs formed from the autoxidation of lipids can be understood based upon a mechanism that involves five different reaction types. These reactions are: reaction of a carbon radical and molecular oxygen, atom transfer of a hydrogen from substrate to the chain carrying peroxyl, fragmentation of the chain carrying peroxyl to give oxygen and a carbon radical, rearrangement of the peroxyl, and cyclization of the peroxyl. The mechanisms of these primary reaction steps has been the focus of extensive research over the past fifty years, and the current level of understanding of these transformations is the subject of this review.